2021
DOI: 10.1021/acs.jchemed.0c01392
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Nitrite in Food and Water Samples Using the Griess Assay and Digital Images Acquired Using a Desktop Scanner

Abstract: The Griess assay is widely used by regulation agencies as an official method for nitrite quantification in water and food samples. In Brazil, the official method, which has been used to determine nitrite in food, was described by Instituto Adolfo Lutz (283/IV) in 1984. It uses 8 mL of reactants and provides 50 mL (reactants plus sample) of waste per sample analyzed. Here, students scaled down the official method 50 times and quantified nitrite in water and food samples by using just 0.2 mL of the Griess reacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…In line with our previous work, we show that any colorimetric assay may be carried out using digital images. One important learning goal in our previous work was the comparison of the standard method with a proposed method, which involved quantitative analysis using digital images.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our previous work, we show that any colorimetric assay may be carried out using digital images. One important learning goal in our previous work was the comparison of the standard method with a proposed method, which involved quantitative analysis using digital images.…”
Section: Introductionsupporting
confidence: 89%
“…The ImageJ plugin ReadPlate extracts R, G, and B values from all wells of the 96-well plate at the same time. Then, all data collected were imported to a Microsoft Excel spreadsheet as shown in our previous works. …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The Griess test involved two chemical reactions for the assay of nitrite. The sulfanilamide first reacted with the nitrite ion in the Griess diazotization reaction to form a diazonium salt, which then reacted with N -1-naphthylethylenediamine dihydrochloride (NED) in an azo coupling reaction to form a soluble reddish-pink azo compound, with a maximum absorption at the wavelength of 540 nm [ 50 ]. Upon treatment of the nitrite-containing meat liquid sample with the Griess reagent for 5 min, the UV-vis absorption of the resulting reddish-pink hue at 540 nm indicated that 1.63 ± 0.17 mg L −1 , 2.50 ± 0.34 mg L −1 , and 3.93 ± 0.34 mg L −1 nitrites were detected in the respective nugget, sausage, and canned meat samples.…”
Section: Resultsmentioning
confidence: 99%
“…Then, all data collected were imported to a Microsoft Excel spreadsheet as shown in our previous works. 48…”
Section: Extraction Of Rgb-values From 96 Microwell Plate Digital Ima...mentioning
confidence: 99%
“…In addition to our previous works, students could quantify the protein content in a series of real-world samples, choose the right standard for each sample, determine LOD and LOQ using different methods, and do an interfering test.…”
Section: Experimental Overviewmentioning
confidence: 99%